Contribution of rainfall vs. water management to Mediterranean wetland hydrology: Development of an interactive simulation tool to foster adaptation to climate variability. (December 2015) - Lefebvre, Gaëtan; Germain, Christophe; Poulin, Brigitte
Abstract: Mediterranean wetlands are increasingly managed to maintain their functions and services following modification in water allocation, embankment and climate change, calling for proactive and adaptive water management. In a first step, we used long-term monitoring of water levels in 37 adjacent embanked marshes in the Camargue as a repeated non-controlled experiment to build a hydrological model. Without information on water input/output by marsh users, we could nevertheless estimate evapotranspiration under flooding and dry conditions, and soil water coefficient. The model provided a high predictive accuracy (adjusted R 2 = 0.73–0.83) of monthly water levels when applied to an independent sample of 12 marshes. In a second step we developed an interactive decision-aid tool that allows users to visualize the impact of their management strategy (desired water level at a specific month) on subsequent water levels, and their consequence on different components of the ecosystem over a 10-yr period. Highlights: Bimonthly monitoring of water levels (37 adjacent marshes, 10 yrs) used to develop a generic hydrological model for Mediterranean marshes fed by surface water. Model validation provided a high predictive accuracy for 12 tested independent marshes. A web interface developed to orient water management, allowing users to visualise impacts on the marsh flora and fauna.